Sesquiterpene lactones and flavonoids with chemotaxonomic significance from Volutaria lippii (L.) Cass. (June 2021) - Rafrafi, Moez; Ben Salah, Hichem; Vougogiannopoulou, Konstantina; Angelis, Apostolis; Skaltsounis, Leandros A.; Allouche, Noureddine
Abstract: Phytochemical investigation on the aerial parts of Volutaria lippii (L.) Cass. led to the isolation of previously undescribed sesquiterpene lactone (1 ), along with other seven known compounds (2 –8 ). Their chemical structures were determined on the basis of MS, IR and NMR spectroscopic data spectra and further supported by comparison with the data descripted in literature. All isolates from the studied plant were mentioned for the first time. This finding could be of chemotaxonomic significance for the genus Volutaria . Highlights: Eight compounds (1–8) were first isolated from V. lippii. The structure of a previously undescribed sesquiterpene lactone (1 ) was established from spectroscopic data. It is the first report of isolation of compounds 1, 3 –6 and 8 from the genus Volutaria. These compounds provide evidence for chemotaxonomic studies of V. lippii and the genus Volutaria.